Effect Of Incubation Time On Blood Group Changes In Blood Stains Contaminated With Aspergillus Flavus - Fakhmi, Shausan Nabila; Khusuma, Ari; Dewi, Lale Budi Kusuma (Poltekkes Kemenkes Mataram, 2024)
Introduction: The change of blood group on the spot is when the non-O blood groups, namely A, B and AB, are found to be blood group O (false), this can occur one of them because of the long time of scattered blood (blood stains) found at the scene of the crime, so it can cause blood stains to be contaminated by mycoorganisms. One microorganism known to easily contaminate bloodstains is Aspergillus flavus. This can lead to the degradation of contaminated bloodstains because the contents in the blood can be used by microorganisms as their metabolic material. Objective : This study examines whether there is an effect of incubation time on changes in blood group in blood spots contaminated with Aspergillus flavus, this study uses blood spots of blood group A and blood group B contaminated with Aspergillus flavus. Method : This study was conducted in vitro and is an experimental study using a one-group pretest-posttest design. Blood spots contaminated with Aspergillus flavus were treated with an incubation period of 1 week, 2 weeks, 3 weeks and 4 weeks. Changes in blood group were then identified using the absorption-elution method. Results : The results of the study as many as 30 units of blood spots of blood group A and blood group B contaminated with Aspergillus flavus did not change the blood group because it can still be identified antigens that match the blood group of the insect at week 4 seen from the occurrence of agglutination. Conclusions : The conclusion that can be drawn from this study is that blood spots of blood groups A and B contaminated with Aspergillus flavus do not change blood groups during incubation times of 1 week, 2 weeks, 3 weeks and 4 weeks or 28 days.